Combined urine metabolomics and 16S rDNA sequencing analyses reveals physiological mechanism underlying decline in natural mating behavior of captive giant pandas - Zhang, Ming-yue; Wang, Xue-ying; Ayala, James; Liu, Yu-liang; An, Jun-hui; Wang, Dong-hui; Cai, Zhi-gang; Hou, Rong; Cai, Kai-lai (Frontiers in Microbiology, 2022)
The decline in natural mating behavior is the primary reason underlying the poor population growth of captive giant pandas. However, the influencing factors and underlying mechanisms remain unclear to data. It is speculated that the decline in natural mating behavior could be related to the psychological stress caused by captivity, which restricts restricting their free choice of mates. In order to test this hypothesis, we performed urinary metabolomics analysis using Ultra-High-Performance Liquid Chromatography-Mass Spectrometry (UHPLC/-MS) combined with 16S rDNA sequencing for exploring the physiological mechanism underlying the decline in the natural mating behavior of captive giant panda. The results demonstrated that the decline in mating ability could be related to abnormalities in arginine biosynthesis, and neurotransmitter synthesis. Additionally, the relative abundance of bacteria from the Firmicutes, Proteobacteria, and Actinobacteria phyla and the Acinetobacter, Weissella and Pseudomonas genus was significantly reduced in the group with low natural mating behavior. These findings imply that the inhibition of arginine synthesis induced by environmental changes could be related to the poor libido and failure of mate selection in captive giant pandas during the breeding period. The results also demonstrate the relationship between the altered urinary microbes and metabolites related to arginine and neurotransmitter synthesis. These findings may aid in understanding the mechanism underlying environment-induced mate selection in captive giant pandas, and propose a novel strategy for determining the sexual desire of giant pandas based on urinary microbes. The method would be of great significance in improving the natural reproductive success rate of captive giant pandas.